Influences of flame-retardant fillers on fire protection and mechanical properties of intumescent coatings - Yew, M.C.; Sulong, N.H.R.; Yew, M.K.; Amalina, M.A.; Johan, M.R. (2015)
A combination of acrylic binder and flame-retardant ingredients was used to synthesize the solvent-borne intumescent coatings designed for steel substrates. The influences of individual and various combinations of flame-retardant fillers on the fire protection and mechanical properties of the coatings were characterized by using Bunsen burner, thermogravimetric analysis, limiting oxygen index, field emission scanning electron microscopy, freeze thaw cycles, static immersion and pull-off type equipment. It was found that the combination of aluminium hydroxide (Al(OH)(3)) and titanium dioxide (TiO2) has significantly improved the fire protection, thermal stability and water resistance of the coating. This formulation had an LOI value of 34, which indicated good flammability resistance of the coating. The adhesion strength tests showed that the coating added with magnesium hydroxide (Mg(OH)(2)) exhibited maximum bonding strength to the metal surface due to its effective interface adhesion. Hence, the findings from this study revealed that the selection of appropriate combinations of flame-retardant fillers strongly influenced the physical and chemical properties of the coatings. (C) 2014 Elsevier B.V. All rights reserved.